Prescribing errors in children – a study of their prevalence, nature and interventions to reduce them - Alenezi, Sattam (2017)
Prescribing errors affect the safety of patients of all ages, however, the risk of prescribing errors may be higher in paediatric patients. This is due to the complexity of calculating doses, age-specific pharmacokinetic and pharmacodynamic changes and the higher usage of unlicensed and off-label medications. This research explores the prevalence and nature of prescribing errors in children and the interventions used to reduce such errors. A multi-centre observational study was conducted to evaluate the prevalence and nature of prescribing errors in paediatric settings. Clinical pharmacists working in thirteen different UK hospitals were asked to identify prescribing errors in inpatient medication orders. The overall error rate was 8.7% of total orders which was similar to the rate of prescribing errors in adults (8.9%) in the EQUIP study. Dosing errors were found to be the most common and the majority of errors were classified as minor. Severity assessment of these errors was conducted by an expert panel to evaluate the severity of all errors which are reported in chapter 2 as data were missing from some of the original error reports. Although there were discrepancies between the panel’s and the original pharmacists’ assessment in 234 of 892 errors, minor errors were still the most common. A second observational study was conducted to evaluate the prevalence and nature of paediatric prescribing errors in electronic medication orders as data for electronic prescribing were only reported from one hospital. Pharmacists were shadowed in their routine clinical work by the researcher who documented all prescribing errors identified by the pharmacists. The overall rate of errors was 5.2% of total orders which was significantly lower than the rate of errors found in the written orders (8.7%) in the previous study conducted in the same hospital using the same methods and before the introduction of an electronic prescribing system. The most common types of errors identified were omission of regular medications on admission followed by under-doses, non-measurable doses and overdoses. Most errors were classified as significant followed by minor errors due to the increased numbers of omission of regular medications on admission. Education is frequently recommended as being key to reducing prescribing errors therefore a systematic review was conducted to identify and evaluate educational interventions which have been used to reduce prescribing errors in children. Only 25 studies met the inclusion criteria. These studies used various educational interventions such as lectures and feedback. Eighteen studies reported that the interventions were effective in reducing errors. Multi-faceted interventions seemed to be more effective than single-strategy interventions. It was difficult to compare the various strategies due to differences in study definitions, denominators and methods of data collection. The impact of interventions is often evaluated by testing the prescribing ability of the doctors involved. A systematic review was therefore conducted to examine the literature on the tests used to assess prescribing competency in doctors caring for children. Only 16 studies met the inclusion criteria. Six studies were designed specifically to evaluate doctors’ dose calculation skills, seven studies used assessments asking the participants to write prescriptions according to given clinical cases and three studies had general questions about prescribing in children. The validity and reliability of the identified tests were not evaluated in any of the studies however. This project has contributed to the field of prescribing errors in children by providing more information about the prevalence and nature of such errors including the most common types and serious errors. Further research is still needed to identify the best ways of avoiding these.